Nyale Sea Worm As Antibacterial Substances - Dwi Soelistya Dyah Jekti; Agus Abhi Purwoko; Zainul Muttaqin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
Nyale is a sea worm that belongs to class of polychaete. It appears on a huge crowd, usually five days after the monsoon in February, at the surface of the sea for breeding. The colors of the female and male worms are green and brown, respectively. The worms are collected in nyale season, freezed-dryer, and extracted with ethyl acetate. Antimicrobial activity properties of the male worm extract are carried out toward benthos bacteria and clinical isolate bacteria using ciprofloxacin as comparing agent. The results show that, after colom chromatography, fraction number 1 and 4 have the best antibacterial activities (broadest spectrum) toward clinical isolate bacteria. All eleven fractions show also antibacterial activities toward nine benthos bacteria. The minimum inhibitory concentration (MIC) of fractions 1 and 4 toward six clinical isolate bacteria is 100 μg/ml. Meanwhile, fraction 4 exhibits two peaks in its HPLC chromatrogram.